Who funds the production of globally visible research in the Global South? - Chankseliani, M (Springer, 2022)
There exist large disparities globally when it comes to knowledge production with very small proportions of publications from the majority world penetrating the global science system. This paper examines the Scopus data on the funders of publications (co-)authored by individuals based in the Caucasus or Central Asia. The analysis shows that in the conditions of scarce local funding for research, research activity has been fuelled by international funding. The funding has been rather diverse and originated from 98 countries across North America, Europe, Asia, Latin America, the Middle East, and Australia. The two countries most frequently mentioned in the funding acknowledgements are the United States and the Russian Federation, cumulatively accounting for approximately 20% of funding acknowledgements. Different types of organisations have funded globally visible research produced by authors based in the Caucasus and Central Asia, most notably bilateral agencies (68% of all funding acknowledgements), followed by philanthropies (7%), and multilateral organisations (5%). This paper offers evidence to question the viability of the narrative of North–South divisions in the global science system. While higher education and research are shaped within territorially bounded, self-contained, and discrete spaces of nation-states, the global science system rests on the extensive flows of funding and knowledge which extend well beyond the nation state.